Isolation of Haemophilus parasuis in lungs of pigs in Lima, Peru: a report of three cases - Pinto J., Chris (2012)
The paper document three cases occurred in May and June, 2006, based on lung samples from pigs of two farms and one slaughterhouse in Lima, Peru. The results of isolation and biochemical test were compatible with Haemophilus parasuis.